Skip to content
Snippets Groups Projects
Commit 4d4db01d authored by Scarlett Gauthier's avatar Scarlett Gauthier
Browse files

Add first 2.5 pages of lecture notes.

parent 61cefa10
No related branches found
No related tags found
1 merge request!9DifferentialEquationsLecture2
Pipeline #41452 passed
......@@ -10,3 +10,142 @@ For this purpose we make the following definitions,
$$y' = \frac{dy}{dx}, \ y'' = \frac{d^2 y}{dx^2}, \ \cdots, \ y^{(n)} = \frac{d^n y}{dx^n}.$$
In the new notation, a linear $n$-th order differential equation with constant
coefficients reads
$$y^{(n)} + a_{n-1} y^{(n-1)} + \cdots + a_1 y' + a_0 y = 0. $$
!!! info "Linear combination of solutions are still solutions"
Note that as was the case for first order linear DE's, the propery of
linearity once again means that if $y_{1}(x)$ and $y_{2}(x)$ are both
solutions, and $a$ and $b$ are constants,
$$a y_{1}(x) + b y_{2}(x)$$
then linear combination of the solutions is also a solution.
In order to solve a higher order linear DE we will present a trick that makes it
possible to map the problem of solving a single $n$-th order linear DE into a
related problem of solving a system of $n$ first order linear DE's.
To begin, define:
$$y_{1} = y, \ y_{2} = y', \ \cdots, \ y_{n} = y^{(n-1)}.$$
Then, the differential equation can be re-written as
$$y_1 ' = y_2$$
$$y_2 ' = y_3$$
$$ \vdots $$
$$y_{n-1} ' = y_{n}$$
$$y_{n} ' = - a_{0} y_{1} - a_{1} y_{2} - \cdots - a_{n-1} y_{n}.$$
Notice that together these $n$ equations form a linear first order system, the
first $n-1$ equations of which are trivial. Note that this trick can be used to
reduce any system of $n$-th order linear DE's to a larger system of first order
linear DE's.
Since we have discussed already the method of solution for first order linear
systems, we will outline the general solution to this system. As before, the
general solution will be the linear combination of $n$ linearly independent
solutions $f_{i}(x)$, $i \epsilon \{1, \cdots, n \}$, which make up a basis for
the solution space. That is the general solution has the form
$$y(x) = c_1 f_1 (x) + c_2 f_2 (x) + \cdots + c_n f_{n}(x). $$
To check that the $n$ solutions form a basis, it is sufficient to verify
$$ det \begin{bmatrix}
f_1(x) & \hdots & f_{n}(x) \\
f_1 ' (x) & \hdots & f_{n}'(x) \\
\vdots & \vdots & \vdots \\
f^{(n-1)}_{1} (x) & \hdots & f^{(n-1)}_{n} (x) \\
\end{bmatrix} \neq 0.$$
The determinant in the preceding line is called the *Wronski determinant*. In
particular, to determine solutions, we need to find the eigenvalues of
$$**A** = \begin{bmatrix}
0 & 1 & 0 & \hdots & 0 \\
0 & 0 & 1 & \hdots & 0 \\
\vdots & \vdots & \vdots & \hdots & \vdots \\
-a_0 & -a_1 & -a_2 & \hdots & -a_{n-1} \\
\end{bmatrix}.$$
It is possible to show that
$$det(**A** - \lambda \mathbbm{1}) = -P(\lambda),$$
in which $P(\lambda)$ is the characteristic polynomial of the system matrix $**A**$,
$$P(\lambda) = \lambda^n + a_{n-1} \lambda^{n-1} + \cdots + a_0.$$
As we demonstrate below, the proof relies on the co-factor expansion technique
for calculating a determinant.
$$- det(**A** - \lambda \mathbbm{1}) = \begin{bmatrix}
\lambda & -1 & 0 & \hdots & 0 \\
0 & \lambda & -1 & \hdots & 0 \\
\vdots & \vdots & \vdots & \hdots & \vdots \\
a_0 & a_1 & a_2 & \hdots & a_{n-1} + \lambda \\
\end{bmatrix} $$
$$- det(**A** - \lambda \mathbbm{1}) = \lambda det \begin{bmatrix}
\lambda & -1 & 0 & \hdots & 0 \\
0 & \lambda & -1 & \hdots & 0 \\
\vdots & \vdots & \vdots & \hdots & \vdots \\
a_1 & a_2 & a_3 & \hdots & a_{n-1} + \lambda \\
\end{bmatrix} + (-1)^{n+1}a_0 det \begin{bmatrix}
-1 & 0 & 0 & \hdots & 0 \\
\lambda & -1 & 0 & hdots & 0 \\
\vdots & \vdots & \vdots & \hdots & \vdots \\
0 & 0 & \hdots & \lambda & -1 \\
\end{bmatrix}$$
$$- det(**A** - \lambda \mathbbm{1}) = \lambda det \begin{bmatrix}
\lambda & -1 & 0 & \hdots & 0 \\
0 & \lambda & -1 & \hdots & 0 \\
\vdots & \vdots & \vdots & \hdots & \vdots \\
a_1 & a_2 & a_3 & \hdots & a_{n-1} + \lambda \\
\end{bmatrix} + (-1)^{n+1} a_0 (-1)^{n-1}$$
$$- det(**A** - \lambda \mathbbm{1}) = \lambda det \begin{bmatrix}
\lambda & -1 & 0 & \hdots & 0 \\
0 & \lambda & -1 & \hdots & 0 \\
\vdots & \vdots & \vdots & \hdots & \vdots \\
a_1 & a_2 & a_3 & \hdots & a_{n-1} + \lambda \\
\end{bmatrix} + a_0$$
$$- det(**A** - \lambda \mathbbm{1}) = \lambda (\lambda (\lambda \cdots + a_2) + a_1) + a_0$$
$$- det(**A** - \lambda \mathbbm{1}) = P(\lambda).$$
In the second last line of the proof we indicated that the method of co-factor
expansion demonstrated is repeated an additional $n-2$ times. This completes the
proof.
With the characteristic polynomial, it is possible to write the differential
equation as
$$P(\frac{d}{dx})y(x) = 0.$$
To determine solutions, we need to find $\lambda_i$ such that $P(\lambda_i) = 0$.
By the fundamental theorem of algebra, we know that $P(\lambda)$ can be written
as
$$P(\lambda) = \overset{l}{\underset{k=1}{\Sigma}} (\lambda - \lambda_k)^{m_k}.$$
In the previous equation $\lambda_k$ are the k roots of the equations, and $m_k$
is the multiplicity of each root. Note that the multiplicities satisfy
$\overset{l}{\underset{k=1}{\Sigma}} m_k = n$.
If the multiplicity of each eigenvalue is one, then solutions which form the
basis are then given as:
$$f(x) = e^{\lambda_1 x}, \ e^{\lambda_2 x}, \ \cdots, \ e^{\lambda_n x}.$$
If there are eigenvalues with multiplicity greater than one, the the solutions
which form the basis are given as
$$f(x) = e^{\lambda_1 x}, \ x e^{\lambda_1 x} , \ \cdots, \ x^{m_{1}-1} e^{\lambda_1 x}, \ etc.$$
\ No newline at end of file
0% Loading or .
You are about to add 0 people to the discussion. Proceed with caution.
Finish editing this message first!
Please register or to comment